2004
DOI: 10.1097/01.wcb.0000125886.48838.7e
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways for Early Brain Injury after Subarachnoid Hemorrhage

Abstract: Few studies have examined the signaling pathways that contribute to early brain injury after subarachnoid hemorrhage (SAH). Using a rat SAH model, the authors explored the role of vascular endothelial growth factor (VEGF) and mitogen-activation protein kinase (MAPK) in early brain injury. Male Sprague-Dawley rats (n = 172) weighing 300 to 350 g were used for the experimental SAH model, which was induced by puncturing the bifurcation of the left anterior cerebral and middle cerebral arteries. The blood-brain ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
173
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 284 publications
(190 citation statements)
references
References 75 publications
5
173
0
2
Order By: Relevance
“…However, the mechanisms that induce the cell death after SAH are still undefined, though inflammation, such as via the MAPKs pathway, has been mentioned as one of the critical mediators. [27][28][29] There is growing evidence that HMGB1 and RAGE signaling and related inflammatory reactions are involved in the pathogenesis of various disorders, including cardiovascular, neurodegenerative, and immune disorders. 12,20,[30][31][32][33] We have recently established that plasma levels of HMGB1 as well as interactions between HMGB1 and RAGE were increased significantly after ischemic stroke onset both in human and mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms that induce the cell death after SAH are still undefined, though inflammation, such as via the MAPKs pathway, has been mentioned as one of the critical mediators. [27][28][29] There is growing evidence that HMGB1 and RAGE signaling and related inflammatory reactions are involved in the pathogenesis of various disorders, including cardiovascular, neurodegenerative, and immune disorders. 12,20,[30][31][32][33] We have recently established that plasma levels of HMGB1 as well as interactions between HMGB1 and RAGE were increased significantly after ischemic stroke onset both in human and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have reported increased activity of all 3 groups of MAPK in cerebral arteries after SAH, but none has examined the time course. 36 It is therefore important to unravel the temporal changes and sequential activation of MAPK. In addition, the event is associated not only with the basal circle of Willis activation (with the blood deposition), but also with the intracerebral microvessels, which may shed more light on the reasons behind the general regional CBF reduction 13,22 and the ischemia which, in people, sometimes is observed despite no angiographic vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…Src tyrosine kinase and the ubiquitous MAPKs are well implicated in brain injury resulting from different causes such as cerebral ischemia, trauma and hemorrhage [2,21,22,24,26,27,31,32,45] and have an important role in cerebral edema [26,31]. Inhibition of src tyrosine kinase with PP1 reduces the expression of vascular endothelial growth factor (VEGF), protects blood-brain barrier, and reduces brain edema immediately after subarachnoid hemorrhage [26] and also offers cerebral protection against stroke by influencing the VEGFmediated vascular permeability and cerebral edema [33]. In this animal model, we have observed a marked effect of PP1 on brain edema as shown in Figure 2.…”
Section: Brain Injuries Produced By This Animal Modelmentioning
confidence: 99%